2020
DOI: 10.1109/access.2019.2963291
|View full text |Cite
|
Sign up to set email alerts
|

A Vehicle Trajectory Tracking Method With a Time-Varying Model Based on the Model Predictive Control

Abstract: The vehicle trajectory tracking algorithm is one of the key and difficult issues of intelligent driving technologies. In current control algorithms for the vehicle trajectory tracking, there are three main assumptions: the standard working condition for the driving path, the same control model used for the entire control process, and a fixed value for the longitudinal vehicle speed. However, the above determinations in current control algorithms are inconsistent with the actual vehicle driving conditions. To o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Some models will also consider the physical and geometric conditions of the road (such as road-friction coefficient and road-line type) and use the vehicle-dynamics model to predict the motion state of the vehicle in the next few seconds. Song et al [1] and Houenou et al [2] presented a trajectory prediction method based on an acceleration-motion model. Sandberg et al [3] and Raigoza et al [4] very recently proposed a novel physics-based trajectory predictor.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some models will also consider the physical and geometric conditions of the road (such as road-friction coefficient and road-line type) and use the vehicle-dynamics model to predict the motion state of the vehicle in the next few seconds. Song et al [1] and Houenou et al [2] presented a trajectory prediction method based on an acceleration-motion model. Sandberg et al [3] and Raigoza et al [4] very recently proposed a novel physics-based trajectory predictor.…”
Section: Literature Reviewmentioning
confidence: 99%
“…MPC algorithm also has many applications in low-speed complex driving conditions [52]. Considering that the longitudinal speed, road curvature, and adhesion coefficient changes under low-speed complex driving conditions have a large impact on the tracking accuracy and stability of unmanned vehicles, the literature [53][54][55] proposed an optimized MPC controller to improve the tracking performance and stability by considering the influence of road constraints, but the study had the problem of being unable to track the reference path with large curvature changes. Therefore, the literature [56,57] proposed the use of Nonlinear Model Predictive Control (NMPC) control method, and the simulation results showed that the tracking performance and stability of the NMPC controller were substantially improved under low-speed large curvature conditions.…”
Section: Pid Algorithmmentioning
confidence: 99%
“…As mentioned above, the accurate trajectory tracking control in AVs requires both the steering wheel control for regulating the lateral position and the throttle/braking control for adjusting its longitudinal dynamics. A vehicle trajectory tracking method with a time-varying model based on the model predictive control using the vehicle kinematic model was proposed in [21]. Random network delay was introduced in [22] to present the uncertainty of the trajectory tracking model of the AV, which significantly deteriorates the stability of the control system and accuracy of the trajectory tracking.…”
Section: Background and Motivationmentioning
confidence: 99%